Understanding Consumer Intentions to Purchase Local and Second-hand Fashion in Indonesia - Wardana, M. Azka Kesuma; Kurniawan, Rudi (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. The fashion industry in Indonesia continues to grow, including trends in local fashion products and second-hand clothing. This study aims to determine the factors that shape consumers' purchase intention towards these fashion products by analyzing the influence of self-efficacy, product specifications, socio-cultural factors, and the mediating role of hedonic motivation. Using a quantitative approach with online questionnaires and purposive sampling (at least 200 respondents), the study used Structural Equation Modeling (SEM) Partial Least Square (PLS) 4.0 for validity testing, reliability, and structural analysis. The results showed that self-efficacy has a significant positive effect on the purchase intention of local fashion products and second-hand clothing. Product specifications and socio-cultural factors have a significant positive effect on purchase intention for local fashion products, but not for second-hand clothing. Hedonic motivation does not mediate the effect of self-efficacy, product specifications, and socio-cultural factors on purchase intention of local fashion products, but mediates the effect of self-efficacy and socio-cultural factors on purchase intention of second-hand clothing. The findings offer insights for marketing strategy and brand management in the local and second-hand fashion industry, emphasizing the importance of consumer trust and specific factors that influence purchase decisions. Keywords: Fashion, local product, second-hand, purchase intention, hedonic motivation Abstrak. Industri mode di Indonesia terus berkembang seiring dengan tren produk fashion lokal dan pakaian bekas. Penelitian ini bertujuan untuk menentukan faktor-faktor yang membentuk minat beli konsumen terhadap produk fashion tersebut dengan menganalisis pengaruh self-efficacy, spesifikasi produk, faktor sosial-budaya, serta peran mediasi motivasi hedonis. Penelitian ini menggunakan pendekatan kuantitatif dengan kuesioner online dan teknik purposive sampling (minimal 200 responden). PLS-SEM digunakan untuk pengujian validitas, reliabilitas, dan analisis struktural. Hasil penelitian menunjukkan bahwa self-efficacy memiliki pengaruh positif signifikan terhadap minat beli pada produk fashion lokal dan pakaian bekas. Spesifikasi produk dan faktor sosial-budaya memiliki pengaruh positif signifikan terhadap minat beli produk fashion lokal, namun tidak terhadap pakaian bekas. Motivasi hedonis tidak memediasi pengaruh self-efficacy, spesifikasi produk, dan faktor sosial-budaya terhadap minat beli produk fashion lokal, tetapi memediasi pengaruh self-efficacy dan faktor sosial-budaya terhadap minat beli pakaian bekas. Temuan ini memberikan wawasan untuk strategi pemasaran dan manajemen merek di industri fashion lokal dan pakaian bekas, dengan menekankan pentingnya kepercayaan konsumen dan faktor spesifik yang memengaruhi keputusan pembelian. Kata Kunci: Mode, Produk Lokal, Second-Hand, Niat pembelian, Motivasi hedonisme